AVAILABILITY OF SPORTS HUMAN RESOURCES REVIEWED FROM SPORTS DEVELOPMENT INDEX IN SAMARINDA - Muhammad Ramli Buhari; Nurjamal Nurjamal; Didik Cahyono; Naheria Naheria; Muhammad Yamin (Faculty of Teacher Training and Education, Mulawarman University, 2021)
The sports development index is one way to measure the improvement of sports development in a region. This research aims to determine the availability of sports human resources in Samarinda City, reviewed from the Sports Development Index (SDI). The study was conducted in five sub-districts in Samarinda City, taking data from three institutions as a scope of research, including the Education Department, the KONI/DIASPORA of Samarinda City, and other Non-Formal Institutions. Research methods use a survey method approach with a quantitative descriptive approach reviewed from SDI. The research instruments used are observation, interview, and analysis of documents. The data obtained is further analyzed using SDI analysis to investigate sports human resources (HR) availability. The results of this study show; The sports HR Index in the Education Department 0.00062 falls into the low category. The HR Index of the KONI/DIASPORA 0.00035 belongs to the low-level category, and the Non-Formal Institutional HR Index 0.000062 belongs to the low-level category. Overall the sports resources index in five sub-districts in Samarinda City of 0.00080 belongs to the low-level category.